PERLAKUAN AKUNTANSI ASET TETAP BERDASARKAN PSAK NO. 16 PADA PT SELECTA - Safi’i, Muhamad Ibnu; Fahriani, Firda Zulfa (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
Businesses are established to produce or distribute goods to help people meet their financialneeds. In any activity, the goal of a company to make a profit cannot be separated from itsbusiness activities. The company always uses fixed assets to carry out operational activitiesso that they run according to their goals. Good and correct application of fixed assetaccounting is used as information for interested parties, so that it requires the best possiblehandling. This study aims to analyze how the accounting treatment for fixed assets andwhether the accounting treatment for fixed assets at PT Selecta is in accordance with PSAKNo. 16. This study uses a qualitative case study method with data collection techniquescarried out by interviews, documentation and observation. The results of the studyconcluded that PT Selecta in carrying out its accounting activities is guided by theAccounting Policy which has led to PSAK No. 16 fixed assets. However, it has not fullyimplemented PSAK No. 16 well. Accounting treatment of fixed assets that are not inaccordance with PSAK No. 16 is that there has never been a reassessment (assetrevaluation), termination and write-off of fixed assets, presentation in the financialstatements. The author recommends that management revaluate assets regularly, write-offassets whose economic useful lives have expired so that the company can ensure that thecarrying amount does not differ at the end of the reporting period.Keywords: Fixed Assets, Financial Accounting Standard, SFAS no.16